Types of organizational culture as predictors of corporate social responsibility - Gunchao Zi (Управление)
Corporate social responsibility has recently become an important part of any organization’s activities. However, organizational culture is undoubtedly crucial and fundamental for the sustainable functioning of organizations. Thus, the purpose of this study was to determine the relationship between organizational culture and corporate social responsibility.Linear regression analysis was used to achieve this goal. Data on four types of organizational culture and the opinions of employees from different enterprises in eight industries were compared using ANOVA variance analysis. Three hypotheses have been put forward that: all types of organizational culture predict the direction of corporate social responsibility “the effectiveness of the organization’s activities in relation to social issues»; all types of organizational culture predict the direction of corporate social responsibility “the organization meets the interests of its agents”; different types of organizational culture dominate in different industries.An empirical study of enterprises in eight industries has shown the relationship between types of organizational culture and corporate social responsibility. Different types of organizational culture dominate in different branches of industry. In addition, certain types of organizational culture are more important for different areas of corporate social responsibility. In the course of the research, the results were obtained, which showed that all the analysed types of organizational culture predict the directions of corporate social responsibility that are responsible for the effectiveness of the organization’s work in relation to social issues and show its effective implementation. The “clan”, “hierarchy”, and “bureaucracy” types of organizational culture provide an opportunity of anticipation of circumstance that the organization respects the interests of its agents. As a result, a model has been developed, that shows their relationship.